Vállalkozóvá váló munkanélküliek jellemzői - Tamás Bakó; Judit Kálmán; Róbert Károlyi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
– This paper examines characteristics for participation in active labor market policies assisting the unemployed in turning into entrepreneurs- among those who were registered unemployed for at least one day during 2014-15 in Hungary. Data shows that it is rather the disadvantaged unemployed who claimed public support for setting up their own business - higher proportions of young entrants and women, lower proportions of higher educated and smaller average social security contributions. According to our result there is a strong relationship between level of education, having an intellectual occupation, former leadership position and becoming an entrepreneur as well as the probabilities for participating in the supportive ALMP program. Thus with or without such support programs those with higher education or special expertise have higher chances for setting up their own business, at the same time they are also the ones who have better chances to claim public support for this. Spatial patterns are also clearly visible: due to EU funding higher amounts of such complex support programs (offering combined training, mentoring and start-up subsidies) were running in convergence regions, hence probabilities for obtaining public support were higher everywhere in the country than in the Central Hungary region. Yet spatial distribution of the program was rather unequal.
Keywords: I38; J47; J48; P11; R58; 330; employment policy; active labour market programs; labour market; entrepreneurship; regional development